2020
DOI: 10.1016/j.jval.2020.04.805
|View full text |Cite
|
Sign up to set email alerts
|

Pmu30 Cost-Effectiveness Analysis of Newborn Screening for Spinal Muscular Atrophy (Sma) in the United States

Abstract: Hospitalized spineinfection patients with a DM diagnosis increased 6%, while discharges with other associated comorbidities decreased. In the group of patients with spine infection and those with DM, the ratio of male/female patients, patient-age distribution, and payer mixes were similar. This was not present for the other comorbidity groups. Conclusions: The frequency of U.S. hospitalizations for spine infection increased between 2006 and 2014. The associated volume of Medicare and Medicaid patients increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Even with the full market cost of gene therapy at AUD 2.73 million (USD 2.1 million), the ICER for NBS with gene therapy would change from the dominant to USD 21,000/QALY, which is still considered cost-effective in the Australian healthcare setting, in the comparison of gene therapy in screened SMA over the current practice of nusinersen therapy without NBS [ 22 ]. Our cost-effectiveness results for NBS with gene therapy compared to no NBS were in line with other published modelling studies in the United States by conference abstracts, indicating that NBS with gene therapy is likely to be cost-effective [ 31 , 32 ]. In the studies examining universal newborn screening for SMA, it has been found that NBS and treatment with nusinersen was not cost-effective, even against higher thresholds for rare diseases, mainly due to the required ongoing treatment maintenance by nusinersen injections [ 21 , 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…Even with the full market cost of gene therapy at AUD 2.73 million (USD 2.1 million), the ICER for NBS with gene therapy would change from the dominant to USD 21,000/QALY, which is still considered cost-effective in the Australian healthcare setting, in the comparison of gene therapy in screened SMA over the current practice of nusinersen therapy without NBS [ 22 ]. Our cost-effectiveness results for NBS with gene therapy compared to no NBS were in line with other published modelling studies in the United States by conference abstracts, indicating that NBS with gene therapy is likely to be cost-effective [ 31 , 32 ]. In the studies examining universal newborn screening for SMA, it has been found that NBS and treatment with nusinersen was not cost-effective, even against higher thresholds for rare diseases, mainly due to the required ongoing treatment maintenance by nusinersen injections [ 21 , 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…Other studies considered either nusinersen and patients with SMA type 1 or onasemnogene abeparvovec alone. 65,66 Furthermore, parameters in this model were adapted to values applicable to the Dutch population. We expect that our model would demonstrate similar results for other countries that share comparable characteristics with The Netherlands.…”
Section: Discussionmentioning
confidence: 99%